2019
DOI: 10.1016/j.ijhydene.2019.04.103
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen fuel cell scooter with plug-out features for combined transport and residential power generation

Abstract: The need for zero emission drive is a global necessity that can contribute to mitigate greenhouse gas emissions. In this context, fuel cell hybrid electric vehicles are increasingly attracting interest by governments, companies and academia. While parked they can operate as power generation units, given the proper connection to the electricity grid via vehicle-to-grid integration (V2G), or even power appliances directly (Vehicle-to-Load, V2L). In this study, we analysed the use of a hydrogen fuel cell electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The remainder of the paper is outlined as follows: linear regression analysis (LRA) [10], [11] and inverse matrix calculation (IMC) [11] for energy demand forecasting are briefly discussed in section 2 of this article. After that, a short description of the research location and the data collection are provided.…”
Section: Figure 1 Power Plant Generation Capacity Expansion Plansmentioning
confidence: 99%
“…The remainder of the paper is outlined as follows: linear regression analysis (LRA) [10], [11] and inverse matrix calculation (IMC) [11] for energy demand forecasting are briefly discussed in section 2 of this article. After that, a short description of the research location and the data collection are provided.…”
Section: Figure 1 Power Plant Generation Capacity Expansion Plansmentioning
confidence: 99%
“…The battery electric bicycle, however, performed environmentally worse during the operating phase [32]. Another benefit of a light-duty hydrogen vehicle such as a FCES was presented by Robledo et al (2019). The authors examined the utilisation of this vehicle type as a V2G or V2L application.…”
Section: Greek Lettersmentioning
confidence: 99%
“…The results showed that using a FCES for a V2L application degrades significantly the FC, while V2G application is more efficient. Moreover, the main conclusion was that although using a FCES as a grid or load support application in conjunction to the typical driving mode is feasible, a new energy management system would be required to be included in the topology [33].…”
Section: Greek Lettersmentioning
confidence: 99%
“…Hydrogen, an eco-friendly and renewable energy source, has gained considerable interest in its wide range of applications, including automobile, fuel cell and space rocket applications [1,2]. However, hydrogen exhibits a colorless, odorless and explosive nature with a low ignition energy (0.02 mJ) and a wide flammable range of 4-74 vol.% in air, leading to many safety issues [3,4].…”
Section: Introductionmentioning
confidence: 99%